The Adoption of Financial Accounting Standards for Small Medium Enterprises by Muslim Entrepreneurs - Muslichah Muslichah; Sunarto Sunarto; Anang Amir Kusnanto; Sri Indrawati; Hariyanto Hariyanto (STIE Malangkucecwara, 2020)
This study aims to discuss the adoption of financial reporting and accounting standards for small-medium enterprises (SMEs) by Muslim entrepreneurs. A structured questionnaire was used to collect quantitative data from the SME owners. 214 Muslim owners of SME businesses participated in the survey. The results show that only a few Muslim entrepreneurs prepared financial reports regularly. The main reason for preparing the statement is for calculating tax, borrowing money, and decision making. An unexpected finding from this study is that most of the Muslim owners are unaware of Standard for SMEs. Users of SME financial reports include tax authority, banks, and owners, or shareholders. This study enriches the financial reporting studies by examining the accounting standards for SMEs in a Muslim dominated country. The findings of this study also have implications for the Institute of Indonesia chartered accountants (IICA) as standard setter. IICA must routinely disseminate these standards to SMEs and also assist them in preparing financial reports